REDUCTION TOTAL ACID NUMBER (TAN) OF SOME SUDANESE CRUDE OILS BY ZEOLITE AND CLAYS - Osman, Waleed Salih Ibrahim (جامعة الوادي - university of el oued, 2015)
The aim of this study was to reduce total acid number (TAN) of some Sudanese crude oils (remove of naphthenic acid) by zeolite and clays. Two sample of zeolite and two samples of clay were used in this study, samples were collected from Hamshcoreep, Glabat and Hatana in east and middle Sudan, and synthetic zeolite was brought from Khartoum refinery. Samples were characterized by X-ray Diffraction (XRD) and the results showed that they are composed of Enstatite, Feldspar, N. Zeolite and synthetic Zeolite. These four samples were used to treat four portions of crude oil (obtained from two types of Sudanese crude oil, Fula blend and Tharjath blend). Total acid number (TAN) of crude oil samples was measured using 484 potentiometric titration instrument (ASTM D644) before and after treatment. One sample of clay, Enstatite, was characterized by Infrared (IR) before and after treatment with crude to insure the presence of acidic material on it after treatment. According to the obtained results, it is evident that Enstatite clay reduced TAN from 1.44mgKOH/g to 0.05mgKOH/g, natural Zeolite reduced TAN from 7.7mgKOH/g to 5.9mgKOH/g, Feldspar reduced TAN from 1.37mgKOH/g to 0.76mgKOH/g, and ZSM-5 Zeolite reduced TAN from 1.98mgKOH/g to 1.57mgKOH/g. In conclusion, all Zeolites and clays used in this study succeeded in decreasing (TAN) of crude oil when they were treated in high temperature (200-220 deg°C.).
Article
Keywords: crude oil, naphthenic acid, total acid number (TAN), Zeolite, Enstatite, feldspar, clay